Geogebra Software: Synergy That Improves Performance in Geometry Learning in Ogbomoso Education Zone of Oyo State - Adigun, Thomas; Aasa, Moses (African Journal of Education and Practice, 2023)
Purpose: This study investigated the effect of GeoGebra software on Mathematics performance of senior secondary school students in Ogbomoso Education Zone 1, Oyo State, Nigeria. Methodology: The research purposes, research questions, and research hypotheses categories each contained three research items.Two (2) public co-education senior secondary schools were chosen using random sampling technique. The experimental group consisted of fifty-three (53) students, consisting of 26 and 27 male and female students, respectively, while the control group consisted of fifty-four (54) students, consisting of 27 male and 27 female students. GeoGebra Learning Approach (GLA) was used to teach the experimental group, whereas the control group received instruction using the conventional learning strategy (CLS). The research instrument utilized for the study was the Mathematics Performance Test in Geometry (MPTG) which was validated by specialists in Mathematics education and Pearson's Product Moment Correlation formula was used to get the index of reliability of 0.78. The data was analyzed using the t-test, mean, and standard deviation. Findings: The study's findings showed that, prior to using Geogebra Software, there was no discernible difference in the students' means performance scores between the two groups. The study also showed a substantial difference between the mean performance scores of students using the Geogebra Learning Approach (GLA) and the Conventional Learning Strategy (CLS) in geometry. The study's final finding showed that there was no statistically significant difference in the mean performance scores of male and female students using the Geogebra Learning Approach (GLA) in geometry. Unique Contribution to Theory, Practice and Policy: Piaget cognitive theory was in conformity with the use of Geogragra Software in teaching mathematics. The study recommends that mathematics teachers should be encouraged to use Geogebra Software and other Information and Communication Technology (ICT) facilities such as power point and projector in teaching their students in order to ease problems of teaching Mathematics.